GIS-based multi-criteria assessment of areas suitable for the construction of a repository for low and intermediate level radioactive waste in Slovenia - Gregorčič Tim; Krevs Marko; Repe Blaž (Geographica Pannonica, 2024)
This study evaluates the site selection for a new repository for low and intermediate level radioactive waste in Slovenia. The ordered weighted average method is used in combination with the TOPSIS method to evaluate the current site and its alternatives considering eight criteria and five constraints. The results show that 52.37% of the country's area falls into five suitability classes for the two decision alternatives, while others do not fulfil the criteria at all. In both cases, the most suitable areas are located in the north-eastern part of Slovenia. The current site tends to be less suitable (categorised as moderately suitable and very unsuitable) and should be reassessed by the relevant stakeholders.